(untitled) - Bertoloni, Calogera; Mba Ekomo, Vitalys; Villemejeanne, Benoît; Lemoine, Charly; Duwald, Romain; Billy, Emmanuel; Mendil-Jakani, Hakima; Legeai, Sophie (Comptes Rendus. Chimie, 2024)
Deep eutectic solvents (DESs) are of particular interest for electrometallurgy processes, since intrinsically conductive and electrochemically stable in a wide range of potentials. Cheaper and greener than conventional ionic liquids, DESs are often bio-sourced and exhibit a higher biodegradability. Ethaline, a DES composed of choline chloride (ChCl) as hydrogen bond acceptor and ethylene glycol (EG) as hydrogen bond donor in 1:2 molar proportions (Et 1:2), is commonly used in electrometallurgy thanks to its good transport properties. However, if ChCl can be considered as a “green” reactant, this is not the case for EG. A DES with a lower toxicity can be obtained by replacing EG by propylene glycol (PG), widely used in cosmetics and pharmacology, yielding a DES called Propeline. The present paper explores the potential of this lesser-known DES in the electrometallurgy of precious metals. Because changing the hydrogen bond donor leads to a modification in the DES bulk properties, the first part of this work deals with the determination of PG-based DESs’ density, viscosity, and conductivity, which are properties of interest for electrochemical processes. The influence of water and PG content is presented and values are compared to those of Ethaline. It appears that ChCl:PG in a molar ratio 1:3 (Pr 1:3) presents the best transport properties. The potentiality of this solvent for the electrometallurgy of precious metals is then discussed: electrochemical stability and electrochemical systems of Ag, Pd, and Au are compared in Pr 1:3 and Et 1:2. Finally, diffusion coefficients of the metallic species and the DES components are given, determined by electrochemical and NMR techniques, respectively.